Reassessment of the phylogenetic relationships of the late Miocene apes Hispanopithecus and Rudapithecus based on vestibular morphology - Urciuoli, Alessandro (Proc Natl Acad Sci U S A, 2021)
Late Miocene great apes are key to reconstructing the ancestral morphotype from which earliest hominins evolved. Despite consensus that the late Miocene dryopith great apes Hispanopithecus laietanus (Spain) and Rudapithecus hungaricus (Hungary) are closely related (Hominidae), ongoing debate on their phylogenetic relationships with extant apes (stem hominids, hominines, or pongines) complicates our understanding of great ape and human evolution. To clarify this question, we rely on the morphology of the inner ear semicircular canals, which has been shown to be phylogenetically informative. Based on microcomputed tomography scans, we describe the vestibular morphology of Hispanopithecus and Rudapithecus, and compare them with extant hominoids using landmark-free deformation-based three-dimensional geometric morphometric analyses. We also provide critical evidence about the evolutionary patterns of the vestibular apparatus in living and fossil hominoids under different phylogenetic assumptions for dryopiths. Our results are consistent with the distinction of Rudapithecus and Hispanopithecus at the genus rank, and further support their allocation to the Hominidae based on their derived semicircular canal volumetric proportions. Compared with extant hominids, the vestibular morphology of Hispanopithecus and Rudapithecus most closely resembles that of African apes, and differs from the derived condition of orangutans. However, the vestibular morphologies reconstructed for the last common ancestors of dryopiths, crown hominines, and crown hominids are very similar, indicating that hominines are plesiomorphic in this regard. Therefore, our results do not conclusively favor a hominine or stem hominid status for the investigated dryopiths.